Physical Activity and Lung Function Growth in a Cohort of Chinese School Children: A Prospective Study. - Jie Ji (Public Library of Science (PLoS), 2013)
Backgrounds/objectives Evidence on the association between physical activity and lung function in children is sparse. The aim of this study was to evaluate children's lung function growth in relation to their physical activity level in Chinese children. Methods A total of 1713 school children aged 9.89±0.86 years who were asthma-free at baseline were followed-up for 18 months from 2006 to 2008 in Guangzhou, China. Information on physical activity and other socio-economic status were obtained from self-administered questionnaires. Lung function tests were performed with a standard procedure. Results At the baseline survey, physically active girls had significantly higher forced vital capacity (FVC) than inactive girls (1.79 l vs. 1.75 l, p<0.05). The growth rates for lung function indices were significantly higher for girls who were physically active at either or both follow-up surveys than those inactive at both surveys during the follow-up period forced expiratory flows at 25% (FEF25) difference per year (dpy) (0.20 l/s vs. 0.15 l/s), forced expiratory flows at 75% (FEF75) dpy (0.57 l/s vs. 0.45 l/s) and forced expiratory flows between 25% and 75% (FEF25-75) dpy (0.36 l/s vs. 0.28 l/s) (all p<0.05). Conclusions Physical activity is positively associated with lung function growth among Chinese school-aged girls. Promotion of physical activity among children is of great importance.